EVALUATING ADHERENCE TO LIFESTYLE AMONG BREASTFEEDING WOMEN IN BABIL PROVINCE, IRAQ - Shabib, M.Sc, Mahmoud Abbas; Ahmed, PH.D, Jabbar Taresh; Alshawi, Ph.D, Raya Habeeb Abdil Imam (PT. Antis International Publisher, 2024)
Background: Lactating mothers are more likely to have nutritional deficiencies and changes in lifestyle during breastfeeding because of altered eating habits, physiological changes, and a variety of sociodemographic variables. Objective: The study aims to assess the impact of lifestyle factors on lactating women and to determine the relationship between socio-demographic variables and the overall lifestyle score. Materials and methods: This study is a descriptive cross-sectional study conducted on 348 mothers selected randomly to evaluate the impact of lifestyle factors on lactating mothers and their infants lower six months during 2023 in primary health care centers in Babylon governorate. The study period was conducted from August 1st to December 1st, 2023. Results: The results of this research indicate that 86% (n=301) of participants had poor lifestyle scores. 14% (n=47) of them have a good lifestyle score, which is the lowest number. Also, these results reveal that urban residents had much higher lifestyle scores than rural. Higher education levels correlated with higher lifestyle scores. Read-and-white students had the fewest high scores compared to high educational level (P. value <0.05). Conclusion: The study indicated that the majority of breastfeeding mothers have poor levels of adherence to a healthy lifestyle. Targeted educational initiatives should educate and assist nursing moms, especially those with lesser education, on the significance of a healthy lifestyle during lactation.